RETRACTED: ARM-Net: Improved MRI brain tumor segmentation method based on attentional mechanism and residual module - Hu, Ming (EAI Endorsed Transactions on e-Learning, 2024)
RETRACTED: The article has been retracted due to misconduct during the peer review process. The retraction notice can be found here:  https://doi.org/10.4108/eetel.12220
Keywords: Brain tumor segmentation; Encoder decoder; Attention mechanism; Residual module